PTU-150 Quality of life before and after intestinal transplantation. (28th May 2012) - Pither, C; Duncan, S; Tincknell, H; Hanson, C; Chukualim, B; Woodward, J; Butler, A; Middleton, S
Abstract : Introduction: Survival following intestinal transplantation has substantially improved over the last decade and if this trend continues quality of life (QOL) may be considered as a major indication for transplantation. It is important to establish if QOL can be enhanced by transplantation and whether some aspects are more inclined to improve than others. Methods: QOL was assessed using Short form 36 (SF36) in a cohort of consecutive patients who had either been assessed for, undergone or, were awaiting transplantation. Data were scored using validated criteria for different QOL functions. The statistical package SPSS (IBM) was used to analyse the data. Results: 62 data sets were available, 26 pre-transplant and 36 post-transplant. Grouped data showed significantly better physical function (p=0.03*), social functioning (p=0.01*), general health (p=0.006*) and emotional role limitation (p=0.02*) in the post-transplant group. Paired pre and post-operative data were available for eight patients: function scores improved significantly for general health (p0.04**). Improvements in physical function, social functioning, emotional role limitations, energy/fatigue, emotional well-being and pain were seen but this did not reach statistical significance. Physical role limitation was the only function to decline. Of the eight pairs, two patients had significantly better overall scores post transplant (p=0.02, p=0.01**) and four had improved overall scores not reaching statistical significance. *independent T test **Wilcoxon signed rank. Conclusion: In this small experience there was an overall trend for better quality of life after transplantation, but certain QOL parameters appear to improve more than others. If quality of life is to be an indication for transplantation it will be important to select patients on the basis of quality of life parameters that are known to improve after transplantation. Longer term and larger studies are required. Competing interests: None declared.